Uma proposta metodológica para o ensino de acentuação gráfica - Santos, Juliana Pereira dos (2010)
This paper aims to propose a methodology for teaching accent according to the rules of the Orthography Agreement of Portuguese Language from 2009. On this perspective, we consider the study of prosody in Portuguese and the guiding principles of the Portuguese spelling fundamental. To support our purpose we will use as an analysis corpus the official text of the agreement spelling of the Portuguese Language from 1990 and the proposal of Silva (2007) for a better organization for disciplinary content. In this sense we present the concepts of molar and molecular used by Silva (2007) to represent two attitudes adopted by the teaching transmitting, the first corresponds to a new methodological approach, the later relates to the traditional, prescriptive teaching of school subjects. Our intention in proposing a new methodology for the teaching of accent is to make it more profitable and efficient for learning and retention of such content by the student of Portuguese Language.